High load inspiratory muscle warm-up has no impact on Special Judo Fitness Test performance - Krauspenhar Merola, P.; Andrade Zaccani, W.; Carvalho Faria, C.; Cortozi Berton, D.; Verges, S.; Franchini, E. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2019)
Background. Respiratory muscles may play an important role in combat sports such as judo in order to meet the high ventilatory demand and to contribute to postural control. Problem and aim. To determine the influence of inspiratory muscle exercise (IMW) as specific respiratory muscle warm-up in a randomized controlled cross-over trial. Methods. 11 judo athletes were assigned to three different warm-up protocols and the effects of IMW on Special Judo Fitness Test (SJFT) were assessed. Each judoka completed three different IMW protocols: uchi-komi warm up (control); warm-up plus IMW (2 sets of 15 breaths with a 60% maximum inspiratory mouth pressure load); uchi-komi warm-up plus sham IMW warm-up (2 sets of 15 breaths with a 15% maximum inspiratory mouth pressure load). The SJFT performance was assessed following each type of warm-up protocol as well as heart rate (HR) and the rate of perceived exertion (RPE). Results. There was no effect of the warm-up protocol on total number of throws (p = 0.141), HR after the test (p = 0.676), HR 1 min after the test (p = 0.543) and performance index (p = 0.240) of the SJFT. However, RPE differed between conditions (p = 0.037), post-hoc Bonferroni tests indicating only a tendency for higher values in the high load IMW condition compared to the control (p = 0.061) and placebo (p = 0.095) conditions. Conclusion. High load IMW did not improve SJFT performance in elite judokas.